Modified Two-Stage Exchange for Periprosthetic Joint Infection in UKA - Andrew G. Yun; Marilena Qutami; Kory B. Dylan Pasko (Case Reports in Orthopedics)
Periprosthetic joint infection (PJI) is a rare complication following unicompartmental knee arthroplasty (UKA), and current management guidelines are still evolving. This report presents a novel surgical technique of resection arthroplasty with an articulated hemispacer as part of a 2-stage exchange protocol. A 66-year-old man developed a culture-negative PJI four months after a medial UKA. Rather than conventional full resection arthroplasty, the patient underwent partial resection with preservation of the lateral and patellofemoral compartments to maintain vascularized bone stock. An articulating hemispacer fashioned from the old implants after sterilization was reimplanted medially to preserve function during the course of antibiotic treatment. After successful eradication of infection, the patient underwent an uncomplicated conversion total knee replacement facilitated by prior preservation of bone stock. No stems or augments were needed. Therefore, a partial resection arthroplasty with an articulating hemispacer used in a 2-stage exchange protocol may be a reasonable option to eradicate infection and maintain function. In future cases of infected UKA, this technique warrants further consideration and investigation.